(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This research included the detection of some variables levels( histamine, serotonin, LOX5 and LTA4H), the effective level of thesevariables on asthmatic group. also the effect antibodies of against inhalation and food allergenswhich leads effective on asthmatic disease. The level of these variables increasesin more asthmatic group than control group also some inhalation and food allergens increase in asthmatic group when compared with control group .